Tenofovir for children and adults with chronic hepatitis B - Li, Huijuan (2023)
Objectives: This is a protocol for a Cochrane Review (intervention). The objectives are as follows:. To evaluate the benefits and harms of tenofovir versus no intervention or placebo for children and adults with chronic hepatitis B.